Tense Arguments: Questions, Exclamations, Emotions - Plantin, Christian (Informal Logic)

(untitled) (Informal Logic, 2019)
Tension is a major issue in the analysis of argumentative discourse in ordinary language. Tension is an operator showing that the speaker is highly involved in her speech, and wants to share her commitments, that is, wants to persuade her audience. This paper proposes a case study of an extremely tense and controversial argument with strong anti-Semitic undertones (§2). The following sections examine the main components of tension: (§3) radicalization of arguments; (§4) exclamations; (§5) rhetorical questions; (§6) emotions. Tension is interpreted as a verdictive operator resisting refutation.